Povezanost specialne motorike s tekmovalno uspešnostjo mladih judoistov - Šimenko, Jožef (Šport (Ljubljana), 2014)
The purpose of the study was to examine the correlations of special motor abilities and competitive performance among young judokas. The sample represented 75 judokas of which were 51 boys and 24 girls. Sample of variables consisted of years of training, age, hand grip strength of the left and right hands in 0° shoulder flexion and 90° shoulder flexion, T test to the left and right, counter-movement jump with hands on the hips, counter-movement jump with the hands swing, squat jump and 100m sprint. Competitive success was defined as final ranking in the overall standings in Slovenian Judo Federation Cup for cadet category. In girls group appeared a moderate correlation between competitive performance and right hand grip strength in 0° shoulder flexion (p 0.01, r = 540) and between competitive performance and right hand grip strength in 90° shoulder flexion (p 0.05, r = 430). In boys group we found a low correlation between competitive performance and countermovement jump with the arm swing (p 0.05, r = 316).
Keywords: agility; agilnost; borilne veščine; borilni športi; combat sports; competitive performance; correlations; hitrost; judo; martial arts; mladina; moč; povezanost; power; speed; sport; šport; športna dejavnost; tekmovalna uspešnost; youth